2021
DOI: 10.2166/wst.2021.074
|View full text |Cite
|
Sign up to set email alerts
|

Green synthesis of Fe nanoparticles by using Mangifera indica extract and its application in photo-catalytic degradation of dyes

Abstract: An exceedingly facile green approach that produces a reliable adsorbent of transition metal such as Iron (Fe) using Mangifera Indica leaf extract at room temperature is described, acquires more significance nowadays. A single pot method used for synthesis with no capping agents, surfactants or other templates. The main intention of this study is to synthesize iron nanoparticles from leaf extract (Mangifera Indica) and examine its degradation potential for photo-catalytic removal of dyes (Congo red & brilli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…For enhanced degradation of L-CHT, different parameters were optimized. The desired amount of nanocatalyst was added (1-5 mg L −1 ) to the L-CHT solution with different concentrations (10-70 mg L −1 ) at a certain pH (5)(6)(7)(8)(9), and the contact time for irritation was 3 h. Aliquots of 3 mL were collected at a regular time interval for 3 h after irritation, and then centrifuged at 4000 rpm for 10 min to remove the photocatalyst from L-CHT. All experiments were conducted in triplicate and showed high reproducibility, with an estimated error of below 5%.…”
Section: Photocatalytic Degradation Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…For enhanced degradation of L-CHT, different parameters were optimized. The desired amount of nanocatalyst was added (1-5 mg L −1 ) to the L-CHT solution with different concentrations (10-70 mg L −1 ) at a certain pH (5)(6)(7)(8)(9), and the contact time for irritation was 3 h. Aliquots of 3 mL were collected at a regular time interval for 3 h after irritation, and then centrifuged at 4000 rpm for 10 min to remove the photocatalyst from L-CHT. All experiments were conducted in triplicate and showed high reproducibility, with an estimated error of below 5%.…”
Section: Photocatalytic Degradation Experimentsmentioning
confidence: 99%
“…The implementation of measures that remove pesticides from agricultural runoff is a must [4]. Several physical and chemical methods have been explored as possible decentralized water treatment technologies, such as filtration or ozonation [5,6]. Unfortunately, the high costs associated with these technologies are a major barrier to implementation in developing countries [5].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the synthesis of iron nanoparticles from leaf extract (Mangifera indica) was examined for its degradation potential for the photocatalytic removal of dyes (Congo red and Brilliant Green) from wastewater. The results showed that the maximum percentage of photo-catalytic degradation achieved was 72.6 and 80.87% for Congo Red, and 72.88 and 82% for Brilliant Green, with biomass and NPs, respectively (Zulfikar et al, 2021). However, in the present study, the decolorization of selected textile dyes was studied without the combination of any other technique.…”
Section: Effect Of Time On Dye Decolorization By Mangifera Indica (L)...mentioning
confidence: 71%